Emergence of NDM-producing Enterobacterales infections in companion animals from Argentina - Juan Manuel de Mendieta; Andrea Argüello; María Alejandra Menocal; Melina Rapoport; Ezequiel Albornoz; Javier Más; Alejandra Corso; Diego Faccone (BMC Veterinary Research, 2024)
Abstract Antimicrobial resistance is considered one of the most critical threat for both human and animal health. Recently, reports of infection or colonization by carbapenemase-producing Enterobacterales in companion animals had been described. This study report the first molecular characterization of NDM-producing Enterobacterales causing infections in companion animals from Argentina. Nineteen out of 3662 Enterobacterales isolates analyzed between October 2021 and July 2022 were resistant to carbapenemes by VITEK2C and disk diffusion method, and suspected to be carbapenemase-producers. Ten isolates were recovered from canine and nine from feline animals. Isolates were identified as K. pneumoniae (n = 9), E. coli (n = 6) and E. cloacae complex (n = 4), and all of them presented positive synergy among EDTA and carbapenems disks, mCIM/eCIM indicative of metallo-carbapenemase production and were also positive by PCR for bla NDM gene. NDM variants were determined by Sanger sequencing method. All 19 isolates were resistant to β-lactams and aminoglycosides but remained susceptible to colistin (100%), tigecycline (95%), fosfomycin (84%), nitrofurantoin (63%), minocycline (58%), chloramphenicol (42%), doxycycline (21%), enrofloxacin (5%), ciprofloxacin (5%) and trimethoprim/sulfamethoxazole (5%). Almost all isolates (17/19) co-harbored bla CTX-M plus bla CMY, one harbored bla CTX-M alone and the remaining bla CMY. E. coli and E. cloacae complex isolates harbored bla CTX-M-1/15 or bla CTX-M-2 groups, while all K. pneumoniae harbored only bla CTX-M-1/15 genes. All E. coli and E. cloacae complex isolates harbored bla NDM-1, while in K. pneumoniae bla NDM-1 (n = 6), bla NDM-5 (n = 2), and bla NDM-1 plus bla NDM-5 (n = 1) were confirmed. MLST analysis revealed the following sequence types by species, K. pneumoniae: ST15 (n = 5), ST273 (n = 2), ST11, and ST29; E. coli: ST162 (n = 3), ST457, ST224, and ST1196; E. cloacae complex: ST171, ST286, ST544 and ST61. To the best of our knowledge, this is the first description of NDM-producing E. cloacae complex isolates recovered from cats. Even though different species and clones were observed, it is remarkable the finding of some major clones among K. pneumoniae and E. coli, as well as the circulation of NDM as the main carbapenemase. Surveillance in companion pets is needed to detect the spread of carbapenem-resistant Enterobacterales and to alert about the dissemination of these pathogens among pets and humans.